2011
DOI: 10.1021/jf201807r
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Treatment of Hydrocarbon-Contaminated Soil Using Biosurfactants from Lactobacillus pentosus

Abstract: The utilization of biosurfactants for the bioremediation of contaminated soil is not yet well established, because of the high production cost of biosurfactants. Consequently, it is interesting to look for new biosurfactants that can be produced at a large scale, and it can be employed for the bioremediation of contaminated sites. In this work, biosurfactants from Lactobacillus pentosus growing in hemicellulosic sugars solutions, with a similar composition of sugars found in trimming vine shoot hydrolysates, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…Low solubility of PETN is the limiting factor for its mobilization and subsequent degradation [2],addition of rhamnolipid led to enhanced mobilization and increase the bioavailability. This is in agreement with the result obtained by [25] who reported that after 15 days the degradation efficiency of octane in soil increased significantly. The authors proposed that mobilization of octane molecules and consequent intensification in their bioavailability was the main reason of the observed differences.…”
Section: Kinetic Studiessupporting
confidence: 93%
“…Low solubility of PETN is the limiting factor for its mobilization and subsequent degradation [2],addition of rhamnolipid led to enhanced mobilization and increase the bioavailability. This is in agreement with the result obtained by [25] who reported that after 15 days the degradation efficiency of octane in soil increased significantly. The authors proposed that mobilization of octane molecules and consequent intensification in their bioavailability was the main reason of the observed differences.…”
Section: Kinetic Studiessupporting
confidence: 93%
“…This is all because of their environmental friendly nature, as they are biodegradable, non toxic, ability to produce from inexpensive raw materials and stable over a wide range of harsh environments. Now a days surfactants are reported for application in many fields of industry -pharmacy, food industry, design of washing agents, petroleum industry, environmental protection and agriculture (Rostas and Blassmann, 2009;Deleu and Paquot, 2004;Singh et al, 2007;Moldes et al, 2011). The biosurfactant produced by microbes are helpful in bioremediation of heavy metal, pesticides and hydrocarbon contaminated sites (Juwarkar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus biosurfactants can be applied in agriculture soil to enhance soil quality. However, high cost for production of biosurfactants yet restricts the application of these green surfactants for bioremediation of soil contaminated by crude oil and/or petroleum [93]. A recent review summarizes the role of biosurfactants and biosurfactants producing microorganisms in bioremediation of heavy metals and hydrocarbon pollutants.…”
Section: Rhamnolipids In Agriculturementioning
confidence: 99%
“…There are several reports on potential properties of biosurfactants produced by Pseudomonas sp, Bacillus sp., and Acinetobacter sp. for removal of heavy metals from contaminated soil and even acceleration of biodegradation of pesticides [87][88][89][90][91][92][93][94]. Rhamnolipids biosurfactants produced by species of pseudomonads are reported to remove toxic metals from soil [95].…”
Section: Rhamnolipids In Agriculturementioning
confidence: 99%